2014
DOI: 10.1158/1940-6207.capr-13-0445
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Cancer Chemoprevention by Withaferin A Is Accompanied byIn VivoSuppression of Self-Renewal of Cancer Stem Cells

Abstract: Current dogma favors elimination of therapy-resistant cancer stem cells (bCSC) for chemoprevention of breast cancer. We showed recently that mammary cancer development in a transgenic mouse model (mouse mammary tumor virus-neu; MMTV-neu) was inhibited significantly upon treatment with withaferin A (WA), a steroidal lactone derived from a medicinal plant. Herein, we demonstrate that the mammary cancer prevention by WA is accompanied by in vivo suppression of bCSC. In vitro mammosphere formation was dose-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 39 publications
4
52
0
1
Order By: Relevance
“…These genes normally function to prevent differentiation of quiescent cells, aiding cancer progression. Whether in monotherapy or in combination effect with cisplatin, WA treatment also resulted in an increase in ROS production and DNA damage, therefore causing cell death and apoptosis in GSLCs [37]. These results reveal the ability of WA to overcome and sensitize the protective barriers exhibited by GSLCs.…”
Section: Safety Considerationsmentioning
confidence: 80%
See 3 more Smart Citations
“…These genes normally function to prevent differentiation of quiescent cells, aiding cancer progression. Whether in monotherapy or in combination effect with cisplatin, WA treatment also resulted in an increase in ROS production and DNA damage, therefore causing cell death and apoptosis in GSLCs [37]. These results reveal the ability of WA to overcome and sensitize the protective barriers exhibited by GSLCs.…”
Section: Safety Considerationsmentioning
confidence: 80%
“…Studies with mice bearing human ovarian tumors have shown that WA alone can preferentially target putative cancer stem-like cells (CSLCs), causing dose-related cell death [36,37]. Furthermore, combining WA with cisplatin resulted in a synergistic effect, reducing tumor size by 70-80 % and preventing metastasis [36].…”
Section: Safety Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…WFA has shown to have potent cytotoxic effects on various cancer cell types. Anticancer activity of WFA has been reported against uveal melanoma [9], glioblastoma cells [10], neuroblastoma and multiple myeloma [11], leukemia [12,13], breast [14][15][16][17], colon [18], ovarian [19], pancreatic [20], prostate [21,22], thyroid [23], and head and neck cancer cells [24].…”
Section: Introductionmentioning
confidence: 99%